THE STUDY OF RELATIONSHIP BETWEEN THE SERUM LEVELS OF SEX HORMONE-BINDING GLOBULIN (SHBG) AND INCREASED INSULIN RESISTANCE IN THE MALE OFFSPRING OF TYPE 2 DIABETIC PARENTS, RISK OF DEVELOPMENT OF DIABETES IN THEIR OFFSPRING - Muhammad Ijaz Anwar; Zafar Hussain; Aftab Ahmad (Journal of University Medical & Dental College, 2015)
ABSTRACT: OBJECTIVE: To determine prospectively the relationship between insulin resistanceand sex hormone binding globulin(SHBG) in connection with risk ofdeveloping diabetes in male offspring oftype 2 diabetics. MATERIALS AND METHODS: This cross-sectional, analytical study included 80 subjects, 40 nondiabetic males (20-30years of age) of single type-2 diabeticparents and 40 age matched healthy male controls without a family history ofdiabetes. For each participant, detailedmedical history and clinical examinationwas performed. Fasting serum glucose,insulin, total testosterone, and sexhormone binding globulin weremeasured using standard kits. Bodymass index and insulin resistance indexwere calculated. For data analysis, groups of young adults(with and without family history of type-2 diabetes) were matched using validcriteria for signiﬁcance of difference. RESULTS: Mean serum insulinconcentration, insulin resistance, body mass index (BMI) and waist circumference (WC) were signiﬁcantlyhigher while sex hormone bindingglobulin levels were signiﬁcantly low instudy subject. Insulin resistancecorrelated inversely with sex hormonebinding globulin. CONCLUSION: Low levels of sex hormonebinding globulin, hyperinsulinemia andinversecorrelation between sexhormone binding globulin and insulinresistance predict the possibledevelopment of diabetes mellitus inmale offspring of type 2 diabetics.